Autonomous Underwater Vehicle Propeller Simulation using Computational Fluid Dynamic. - Husaini, Muhamad; Samad, Zahurin; Arshad, Mohd Rizal (Intech, 2011)
Recently AUV development was stressed on improving the operation range and time.